2020
DOI: 10.1002/alz.043387
|View full text |Cite
|
Sign up to set email alerts
|

Gamma power increased in Alzheimer's disease patients in comparison to healthy controls during recognition of facial expressions

Abstract: Background Several researchers have reported the impairment of recognition of facial expressions in Alzheimer’s disease (AD) patients. AD had reduced theta and alpha responses compared to healthy controls during the recognition of facial expressions (Güntekin et al. 2019). Gamma responses also have a crucial role in the recognition of facial expression in healthy young adults (Güntekin and Başar 2014). AD had increased late gamma responses compared to healthy controls during working memory paradigms (Başar et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, in depression, both HFD (Akar et al, 2015) and power (Strelets et al, 2007) in gamma band increases, indicating a positive correlation. Similarly, reduced HFD in AD (Smits et al, 2016) and increased gamma power during resting state (van Deursen et al, 2008; Güntekin et al, 2020; Fide et al, 2021) hint at a negative correlation. PCeske and colleagues surveyed several studies and found HFD to be negatively correlated with theta, alpha and beta band power but weakly positively related to gamma band power (Päeske et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…For example, in depression, both HFD (Akar et al, 2015) and power (Strelets et al, 2007) in gamma band increases, indicating a positive correlation. Similarly, reduced HFD in AD (Smits et al, 2016) and increased gamma power during resting state (van Deursen et al, 2008; Güntekin et al, 2020; Fide et al, 2021) hint at a negative correlation. PCeske and colleagues surveyed several studies and found HFD to be negatively correlated with theta, alpha and beta band power but weakly positively related to gamma band power (Päeske et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Information judgment is to study the conveyed meaning by facial expressions (such as happy, angry, or sad). Indication judgment is to study physical signals, which are used to convey information (such as raised cheeks or sunken lips) [15][16][17]. e main disadvantage of the information judgment method is that it cannot explain the full range of facial expressions.…”
Section: Introductionmentioning
confidence: 99%